Consumer reactions to price discounts across online shopping experiences. (November 2019) - Sheehan, Daniel; Hardesty, David M.; Ziegler, Alexander H.; Chen, Haipeng (Allan)
Abstract: Consumers generally encounter a multitude of price discounts during a single visit to a retailers' website, yet past research has predominantly examined price discounts in a singular manner. We examine how the influence of a price discount's magnitude on consumer purchase intentions evolves during an online shopping trip. In doing so, we demonstrate that a price discount's magnitude is less predictive of consumers' purchase intentions earlier, but it becomes more predictive later, during an online shopping trip. Thus, placing shallow price discounts early in a shopping visit may enhance the effectiveness of a firm's portfolio of price discounts.